DAMPAK TINDAK PIDANA CYBERBULLYING TERHADAP KORBAN DAN PELAKU DITINJAU DARI PERSPEKTIF VIKTIMOLOGI DAN KRIMINOLOGI - Dippo Alam (SUPREMASI HUKUM, 2022)
In Indonesia, almost everyone has a gadget or more specifically, a smart cellular phone that is connected to the internet network very easily. Cyberbullying is a way of bullying that involves sophisticated digital technology, which almost always uses the internet as a tool. Cyberbullying is characterized by aggressive behavior carried out by a person or several people using electronic media services including the internet, which is carried out continuously, where the target victim is someone who is considered weak or unable to fight back. The forms of cyberbullying are usually in the form of ridicule, insults, threats or intimidation. The perpetrators of cyberbullying have the motivation to take these actions in the form of anger and revenge, frustration, wanting to be the center of attention of the surrounding environment, mere entertainment, or even just joking with the victim. Victims of cyberbullying often experience a number of psychological problems to even think of committing suicide. The problems that arise are how severe the cyberbullying behavior is in damaging the victim's psychology and/or physical appearance from the perspective of victimology and how to mitigate cyberbullying and take action against the perpetrators from a criminological perspective. The author conducted a qualitative research in which this research is descriptive analytical. Victims of cyberbullying have committed suicide. If it turns out that cyberbullying is felt to be very worrying, then what needs to be done is to capture a screen display containing bullying carried out on social media, be it via a smartphone or computer, then report it to the police. Victims of cyberbullying should receive treatment from professionals such as psychologists, psychiatrists, even the police and the Witness and Victim Protection Agency. The author recommends appropriate punishment for perpetrators who openly cyberbullying in accordance with the ITE Law, because some of them do not regret and even enjoy their actions. Keywords: Cyberbullying, criminology, victimology